2013
DOI: 10.1097/opx.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Aberration and the Sign of Defocus

Abstract: When coupled with Wallman's hypothesis that retinal activity caused by image contrast inhibits eye growth, these results provide a testable hypothesis to account for myopia progression. For example, we suggest that hyperopic blur is a risk factor for myopia progression only when the eye has a negative SA because that is the combination leading to relatively low contrast in the defocused retinal image. Because the likelihood of a negative SA increases with accommodation, avoiding long hours of near work in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 75 publications
(49 reference statements)
3
43
0
2
Order By: Relevance
“…Spherical aberration values of −0.2 to −0.3 μm or less (more negative) for a 5-mm pupil required clinically significant changes (at least 0.25 D) in the best sphere correction to optimize the retinal image quality. Thibos et al 40 also performed computational modelling and investigated the coupling effect of the sign of spherical aberration and defocus on retinal image quality. They reported that positive spherical aberration may have a protective effect against myopia progression because, in combination with hyperopic defocus that is often present in young myopes with a lag of accommodation during near work, 41,42 this improved the retinal image quality in comparison with the combination of negative spherical aberration and hyperopic defocus.…”
Section: Discussionmentioning
confidence: 99%
“…Spherical aberration values of −0.2 to −0.3 μm or less (more negative) for a 5-mm pupil required clinically significant changes (at least 0.25 D) in the best sphere correction to optimize the retinal image quality. Thibos et al 40 also performed computational modelling and investigated the coupling effect of the sign of spherical aberration and defocus on retinal image quality. They reported that positive spherical aberration may have a protective effect against myopia progression because, in combination with hyperopic defocus that is often present in young myopes with a lag of accommodation during near work, 41,42 this improved the retinal image quality in comparison with the combination of negative spherical aberration and hyperopic defocus.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] It has been hypothesized that the increase in positive SA could provide an additional explanation for the myopia control effects obtained with different treatments in progressing myopes, due to a change in behavior of the accommodative system. [36][37][38] However, there is controversy in the results from different studies aiming to evaluate the actual changes in the accommodative system after Table 2. The slope of the linear regressions is indicative of the direct relation between refractive descriptors.…”
Section: Discussionmentioning
confidence: 99%
“…7,23 Thibos et al hypothesize that hyperopic blur can be a risk factor for the progression of myopia when the eye has a negative spherical aberration (which can lead to low contrast in a defocused retinal image). 24,25 Changes in ocular wavefront aberrations occur as accommodation attempts to compensate for retinal defocus. 11 The average change in defocus in the present study showed a clear negative relationship with increasing accommodation stimuli.…”
Section: Discussionmentioning
confidence: 99%